Some Current Developments in Brazilian Sociology of Crime: Towards a Criminology? - Freitas, Renan de; Ribeiro, Ludmila (International Journal of Criminology and Sociology, 2014)
This paper discusses the directions taken by sociology of crime in Brazil ever since its appearance, in the dawn of the 1970s, as well as the factors that prevented the development of a true criminology in the country, similar to that already found in North America. It is herein argued that while, on the one hand, Brazilian sociology was indeed able to develop an agenda of research on the processes that account for the criminalization of poorer segments of the population, on the other hand, for not having paid due attention to an entire consolidated body of knowledge available in order countries, it failed to explain rises and declines in criminality rates, and likewise failed to prescribe effective related public policies.